Retrospective analysis of donor deferral for plateletpheresis at a regional transfusion center, in North-West India - Pal, Ashok; Bundas, Sunita; Handa, Anjali; Meena, Udai Singh (International Journal of Research in Medical Sciences, 2021)
Background: Single donor platelet (SDP) is one of the valuable component for thrombocytopenic patients for obtaining good post transfusion count increment, good yield of product is required. Proper donor selection has a crucial role in in safety and quality of product therefore proper screening of donor is mandatory. The aim was to find out reasons and frequency of plateletpheresis donor deferral and to encourage safety of donor for recruitment of new SDP donors. Methods: A retrospective analysis of data was done over a period of 1 year from June 2018 to May 2019 from the data centre of the institute. Results: Out of 1365 donors, 1200 were selected for plateletpheresis procedure and remaining 165 donors were deferred for various reasons. The predominant age of donors ranges from 25-35 years. Among the deferred donors temporary donors accounted for 93.33% and permanently deferred donors were 6.61. Most common cause for deferral were poor venous access 52 (31.51%). Low platelet counts 32 (19.39), low Hb 26 (15.75%), underweight 24 (14.54%), under medication 9 (5.45%), alcohol intake within 24 hours 6 (3.63%) and others like tattoos, infections/inflammations at phlebotomy sites 5 (3.03%) and most common reason for permanent deferral were sero-positivity for HbsAg 6 (3.63%), chronic diseases 4 (2.42%) (cardiovascular diseases bronchial asthma), others 1 (0.6%). Conclusions: For obtaining good yield of product, proper donor screening is required. Temporary deferred donors should be counselled properly and encouraged for further donation when comes under selection criteria. Donor selection criteria for apheresis may be revised.